Aspectos morfológicos, fisiológicos e produtivos de acessos de Opuntia spp. com resistência à Dactylopius opuntiae, no semiárido brasileiro - Santos, João Paulo de Oliveira (2023)
Opuntia is one of the most important genera of Cactaceae, standing out for its potential for producing vegetables and fruits for human consumption, and foraging purposes of many of its species. In Brazil, the introduction of the false carmine cochineal (Dactylopius opuntiae) in areas producing some species of this genus, caused serious production losses, which resulted in the need to search for and introduce varieties with resistance to this pest. In this sense, this study was divided into 3 chapters. In chapter I, we sought to evaluate the initial performance of 15 accessions of Opuntia with resistance to D. opuntiae in terms of morphological, physiological and productive aspects, thus seeking the early selection of materials with superior characteristics. In chapter II, the objective was to carry out the morphological and productive characterization of these accessions 365 days after planting (DAP). In chapter III, the objective was to analyze the physiological aspects and the dry matter production of these accessions also at 365 DAP. The experiment was carried out under field conditions at the Experimental Station of Pendência, belonging to the Empresa Paraibana de Pesquisa, Rural Extension and Land Regularization, in the municipality of Soledade, Paraíba. The results obtained were submitted to analysis of variance and subsequent test of means. Principal component analyzes (PCA) were also used. The results showed that 180 days after planting, it is already possible to identify Opuntia accessions with superior characteristics, such as accessions 48, 49, 75, 91 and 100, which reached fresh matter production greater than 40 t ha-1. At 365 DAP, the PCA showed that morphological characters, such as height and width of plants, as well as cladode area and IAC, are directly related to greater production of green matter, which was greater than 108 t ha- 1 in accessions 48, 49, 75, 91 and 100. Still, for the physiological aspects, the PCA showed that for the accessions under study, a higher concentration of pigments is related to higher rates of CO2 uptake, greater instantaneous efficiency of water use and, therefore, higher dry matter productivity.